Field testing of morphing flaps on a wind turbine blade using an outdoor rotating rig. (April 2019) - Ai, Qing; Weaver, Paul M.; Barlas, Thanasis K.; Olsen, Anders S.; Madsen, Helge A.; Andersen, Tom L.
Abstract: In recent years, active flap devices on wind turbine blades have been shown to both reduce peak loads at the tower and extend blade fatigue life. Associated benefits include retrofitting existing tower infrastructure with longer and greater energy-producing blades whilst also extending service life of blades. In the current work, a novel wind turbine blade control method using morphing flaps has been successfully investigated and demonstrated using a scaled demonstrator mounted on an outdoor rotating test rig. Shape adaptive structures that remain conformal to the flow are increasingly referred to as morphing devices. As part of the INNWind.eu project, a novel morphing flap device was developed for a recently designed aerofoil. The proposed morphing flap comprises a light-weight carbon fibre laminate, 3D printed honeycomb core and a flexible silicone surface. A comprehensive test campaign using an outdoor rotating test rig under atmospheric conditions was carried out to assess the potential effectiveness. As shown by experimental data, the morphing flap provides good performance in terms of aerodynamic lift control of the blade and can provide dynamic load alleviation capability. Highlights: The application of morphing structures for simultaneous improvement of the aerodynamic performance of wind turbine blades. Design, modelling and prototyping of a morphing flap concept using 3D printed honeycomb core and carbon fibre laminate. Outdoor testing of morphing flaps mounted on a blade section using a rotating testing rig in field for realistic effects. Results confirmed the aerodynamic enhancement and the dynamic load alleviation effects using the proposed morphing flaps.